Engineering silicon crystals for photovoltaics. Issue 9 (11th February 2016) - Lan, C. W.; Yang, C. F.; Lan, A.; Yang, M.; Yu, A.; Hsu, H. P.; Hsu, B.; Hsu, C.
Abstract : In this highlight, we review the recent engineering efforts in the state-of-the art industrial production of customized silicon crystals, including quasi-mono and multi-crystalline silicon (mc-Si). Abstract : Silicon has remained the material of choice for both the microelectronic and photovoltaic (PV) industries for a few decades. In addition to its abundance, silicon can be refined to an extremely high purity and grown into large dislocation-free single crystals that meet the stringent requirements of modern electronic devices for many applications. On the other hand, customized silicon crystals with lower purity and perfectness, grown via high-throughput directional solidification at a low cost, that can meet the high performance needs of solar cells have rapidly driven PV development in the past decade. In this highlight, we review the recent engineering efforts in the state-of-the art industrial production of customized silicon crystals, including quasi-mono and multi-crystalline silicon (mc-Si). Special attention will be focused on the so-called high-performance (HP) mc-Si that has become the mainstream material for solar cells since 2012.